2016
DOI: 10.1038/srep19699
|View full text |Cite
|
Sign up to set email alerts
|

High dose CD11c-driven IL15 is sufficient to drive NK cell maturation and anti-tumor activity in a trans-presentation independent manner

Abstract: The common gamma (γc)-chain cytokine interleukin 15 (IL15) is a multifunctional immune-modulator which impacts the generation, maturation and activity of many cell types of the innate, as well as the adaptive immune system, including natural killer (NK) and CD8+ T cells. Using a new series of transgenic mice, we analyzed the in vivo potential of IL15 as an immune-regulator when available at different concentrations or delivery modes, i.e. soluble monomer or complexed to its specific receptor α (Rα)-chain. We h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
23
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(23 citation statements)
references
References 47 publications
0
23
0
Order By: Relevance
“…Following the production of new NK cells in the bone marrow, immature NK cells undergo a maturation process driven by the cytokine IL-15, which is characterized by the acquisition of the surface marker CD11b, loss of CD27, and increased proliferation and survival (Figure 3F) (Chiossone et al, 2009; Polansky et al., 2016). Ablation of the Rroid locus resulted in a block of NK cell maturation characterized by accumulation of immature CD27 + NK cells and a near complete loss of mature CD11b + NK cells (Figure 3F–G).…”
Section: Resultsmentioning
confidence: 99%
“…Following the production of new NK cells in the bone marrow, immature NK cells undergo a maturation process driven by the cytokine IL-15, which is characterized by the acquisition of the surface marker CD11b, loss of CD27, and increased proliferation and survival (Figure 3F) (Chiossone et al, 2009; Polansky et al., 2016). Ablation of the Rroid locus resulted in a block of NK cell maturation characterized by accumulation of immature CD27 + NK cells and a near complete loss of mature CD11b + NK cells (Figure 3F–G).…”
Section: Resultsmentioning
confidence: 99%
“…5,49,50 Indeed, as speculated earlier, 4 it is possible that in inflammatory conditions an increase in IL-15 production could override the mechanism of trans presentation. 51,52 Moreover, the presumably prominent role of trans presentation is supported by the hypothesis that IL-15 in the circulation predominantly, if not only, exists as a heterodimer with IL-15Ra. 38 This is, however, not always the case, as we demonstrate here that intranasal Aspergillus administration to mice triggers an increase in both free and IL-15Ra-bound IL-15 circulating levels.…”
Section: Discussionmentioning
confidence: 96%
“…However, there are other reports indicating that IL-15 also participates in the growth and survival of malignant cells in hematopoietic malignancies and solid tumors ( 20 , 21 , 61 , 62 ). The protumoral activity of IL-15 may be underestimated since most of the analyses to study IL-15 function are using immune-sufficient mice and focus on its effect on CD8 T cells or NK cells ( 12 , 13 , 16 , 17 ). However, it has been reported that GM-CSF and IL-15 fusokine is an immunosuppressor and allow engraftment of allogeneic B16F10 in immunocompetent mice ( 62 ).…”
Section: Discussionmentioning
confidence: 99%
“…IL-15 exhibits broad activity and induces the differentiation and proliferation of lymphocytes ( 1 , 7 ) and myelocytes ( 8 , 9 ). The studies of mutant mice deficient in IL-15 or IL-15Rα suggest that IL-15 play a multifaceted role in the development and control of the immune system ( 10 13 ). Thus, IL-15 has become a promising candidate for tumor immunotherapy; IL-15 administration is used to bolster immune responses ( 14 , 15 ) and augment the tumor immune surveillance ( 16 , 17 ).…”
Section: Introductionmentioning
confidence: 99%